The Educational and Occupational Expectations of Rural Ohio Tenth- and Twelfth-Grade Students - Kerry S. Odell (Journal of Research in Rural Education, 1988)
The major purpose of this study was to identify the educational and occupational expectations of rural Ohio tenth- and twelfth-grade secondary school students. Extent to which relationships existed between the educational and occupational expectations of these students and personal, family, and school characteristics were also investigated. Using a researcher developed questionnaire, usable data were collected from 491 tenth- and twelfth-grade students. Results of this study indicated that rural students had educational and occupational expectations that were higher than the attainments of their parents. Over 60 percent of the students reported that they were likely to attend college. Students expected to enter occupations with much higher status scores than the occupations in which their parents were presently employed. Educational and occupational expectations of the rural students were found to have low to substantial associations with gender, type of high school program enrollment, high school grade point average, parental occupations, parental education attainments, and parental expectations.